2018
DOI: 10.1021/jacs.8b10977
|View full text |Cite
|
Sign up to set email alerts
|

Optically Active Inverse Opal Photonic Crystals

Abstract: Chiral photonic crystals have been a widely investigated topic in chemistry, physics and biology. Till now, the research about chiral photonic crystals has been conducted on the objects of helical structures, while the chiral photonic crystals made of periodic chiral media remain unexplored experimentally. In this work, we have successfully constructed three-dimensional chiral polymer inverse opal photonic crystals (3D CPIOPCs) by a template-based method. Impressively, the 3D CPIOPCs exhibit emerging circular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 27 publications
0
28
0
Order By: Relevance
“…[91][92][93][94][95] Chirality is ubiquitous at various hierarchical levels from the galactic, macroscopic, nanoscopic, supramolecular to molecular and subatomic scales. [96][97][98][99] It is worth noting that CNCs are typically nanoscale chiral photonic crystal materials that can be isolated from various natural plants and wood. It is a highly crystalline nanorod with a high aspect ratio that can self-assemble and form a left-handed chiral nematic LC in a water suspension.…”
Section: Nanocellulose-based Chiral Photonicsmentioning
confidence: 99%
“…[91][92][93][94][95] Chirality is ubiquitous at various hierarchical levels from the galactic, macroscopic, nanoscopic, supramolecular to molecular and subatomic scales. [96][97][98][99] It is worth noting that CNCs are typically nanoscale chiral photonic crystal materials that can be isolated from various natural plants and wood. It is a highly crystalline nanorod with a high aspect ratio that can self-assemble and form a left-handed chiral nematic LC in a water suspension.…”
Section: Nanocellulose-based Chiral Photonicsmentioning
confidence: 99%
“…On the other hand, the structural colors of PCs were also reported as latent templates for applications in anti-counterfeiting because of their unique periodicity and viewing angle-dependent optical properties. 21–30 Qin et al reported angle-dependent structural colors to provide rich optical information, thus producing a rainbow-color chip to obtain convenient recognition of multiple analytes. 31 Meng et al prepared a flexible polyvinylidene fluoride (PVDF) anti-opal structure color film with angle dependence.…”
Section: Introductionmentioning
confidence: 99%
“…Necessary optical manipulation in photonic crystals is especially important for the development of intelligent photoswitch devices. , Inspired by nature, , considerable studies are focused on the development of periodic dielectric materials with photonic band gaps, , which prohibit the propagation of photons having energies within the band gap region . The color transformation of most photoswitches depends on the blueshift (or redshift), , superposition, , or environmental stimulated formation of the photonic band gap. , The patterned photonic crystals with changing band gaps open a new field for the preparation of high-performance materials and functional photoswitch devices. These varying band gaps are related to the assembly form of nanoparticles, such as magnetic and Langmuir–Schaefer assemblies . It also relies on some methods of physical transformation, including polymer scaffold, glass transition, and deformable microspheres .…”
Section: Introductionmentioning
confidence: 99%